NEOLITHIC CERAMICS OF THE CHOKH SETTLEMENT IN THE CONTEXT OF CERAMIC TECHNOLOGICAL TRADITIONS OF THE EASTERN CAUCASUS - Petrova, Natal'a Ur'evna; Sajpudinov, Murad Sahbanovic; Karpova, Evgenia Vladimirovna; Babenko, Anna Nikolaevna; Kosorukov, Vladimir Leonidovic; Guliev, Farhad El'dar ogly; Sagitova, Dzavadovna Mar'am (History, Archeology and Ethnography of the Caucasus, 2024)
The purpose of this article is to study the place of Neolithic ceramics of the Chokh settlement among the cultural and technological traditions of the Neolithic ceramics of the Caucasus, as well as its role in the formation of ceramic production of Central Dagestan. In this regard, in the course of this work, using technological, photographic, XRD and spherulite analyzes, a comparative study of Neolithic ceramics from Chokh settlement was carried out with products from the closest Neolithic settlement of Transcaucasia – Göytepe, located in the middle reaches of the Kura River, as well as with later ceramic materials from the Chalcolitic and Bronse Age periods of Central Dagestan. The analysis of Neolithic ceramics from the Chokh settlement, on the one hand, showed that it is entirely an item of local production, which is determined by the characteristics of the raw materials, and the admixture of grog in the pottery paste. On the other hand, connections with one of the types of Transcaucasian ceramics from the settlements of the early 6-th millennium BCE, Haci Elamxanli Tepe and Gadachrili Gora – products with mineral admixture and, possibly, dung in the pottery paste, fired mostly in reducing atmosphere with applique buttons on the surface are presumably recorded. This type continued to exist in later Göytepe materials with some changes. Further, in the pottery production of Central Dagestan during the Chalcolitic – Bronze Age period, on the one hand, we can talk about the gradual development – the replacement of mineral admixtures, the appearance of polishing tradition and improvement of firing conditions.
Keywords: Chokh; Neolithic of the Caucasus; Mountainous Dagestan; Chalcolithic of Dagestan; Bronze Age of Dagestan; Transcaucasia; Göytepe; ceramics